A model of housing and credit cycles with imperfect market knowledge - Pei Kuang (University of Birmingham, Birmingham Business School, 2014)
The paper presents a model of housing and credit cycles featuring distorted beliefs and comovement and mutual reinforcement between house price expectations and price developments via credit expansion/contraction. Positive (negative) development in house prices fuels optimism (pessimism) and credit expansion (contraction), which in turn boost (dampen) housing demand and house prices and reinforce agents' optimism (pessimism). Bayesian learning about house prices can endogenously generate self-reinforcing booms and busts in house prices and significantly strengthen the role of collateral constraints in aggregate fluctuations. The model can quantitatively account for the 2001-2008 U.S. boom-bust cycle in house prices and associated household debt and consumption dynamics. It also demonstrates that allowing for imperfect knowledge of agents, a higher leveraged economy is more prone to self-reinforcing fluctuations.
Keywords: D83; D84; E32; E44; 330; Boom-Bust; Collateral Constraints; Learning; Leverage; Housing